The effect of high flow nasal cannula vs continuous positive airway pressure oxygen support in COVID-19 pneumonia in central South Africa - Cassim, Shaaista (University of the Free State, 2023)
𝗜𝗻𝘁𝗿𝗼𝗱𝘂𝗰𝘁𝗶𝗼𝗻: The sudden escalation of COVID-19 pneumonia proved to be a great challenge for an already taxed health system in Central South Africa. With minimal ICU beds and in resource limited hospitals, the use of non -invasive ventilation was soon identified as the attractive alternative. Thus, high flow nasal oxygen (HFNO) and continuous positive airway pressure (CPAP) were important forms of supplementary oxygen therapy for patients with COVID-19 pneumonia. Due to the limited data at the time on the pathophysiology of the disease with regards to the types of pneumonia as well as the concept of patient self-induced lung injury, it was difficult to formulate treatment guidelines as well as ventilation strategies. There existed no clear point for the escalation of management or for the prognostications of patients. In order to properly utilize resources and to ensure adequate treatment this study was conducted. The aims of the study were to compare the outcomes of patients on HFNO to those receiving CPAP and to investigate the limitations of HFNO and CPAP therapy and modes of failure leading to death needs to be identified. The study also aimed to evaluate the practices in both high flow nasal oxygen and continuous positive airway pressure to explore the optimal point for escalation or failure. 𝗠𝗲𝘁𝗵𝗼𝗱𝘀: This retrospective observational single centre study was conducted in a field hospital , House Idahlia in the Free State. A total of 146 adult patients with respiratory failure due to severe COVID-19 pneumonia were treated with either HFNO or CPAP as initial treatment. Respiratory failure due to severe COVID-19 pneumonia was defined as a respiratory rate of more than 30 breaths per minute, oxygen saturation of less than 93% despite oxygen flow of 15l/min via reservoir bag or an SpO2/FiO2 ratio of less than 150. Due to the severe lack of resources there was no access to radiology. Automated monitoring systems recorded observations and minimized the number of nursing staff required. Demographics , infective markers, APACHE scores and length of stays were analyzed for all patients. Outcomes and survival related to the respiratory rate oxygenation (ROX) scores were analyzed and compared. The oxygen saturation, respiratory rate, flow rate, CPAP and respiratory swings were recorded in all patients who received CPAP. The respiratory swing was used as a surrogate for the transpulmonary pressure to assess the presence of patient self-induced lung injury These endpoints were used in a multivariate analysis to explore possible endpoints predicting death or discharge. 𝗥𝗲𝘀𝘂𝗹𝘁𝘀: The overall survival was 45,3%. Both groups were comparable with regards to demographics, baseline bloods and APACHE scores. All patients presented with severe respiratory failure as depicted with an SpO2/FiO2 ratio of less than 150. All patients with a ROX score > 3.85 survived. With a ROX score < 3.85 showing an overall mortality was 67,3%. A sustained respiratory rate >30 breaths/min, respiratory swings >10 cmH2O, CPAP >10 cmH2O for more than 2-days and flow rates of more than 60 l/min were associated with increased mortality. 𝗖𝗼𝗻𝗰𝗹𝘂𝘀𝗶𝗼𝗻: Non-invasive ventilation supplementary oxygen is a cost effective and reasonable strategy to manage patients with severe COVID- 19 pneumonia. Patients with sustained hyperventilation, high O₂-flows, and CPAP >10 cmH2O combined with a sustained respiratory swing of >10 cmH2O have poor outcomes on HFNO and CPAP. These patients must be considered for early intubation and mechanical ventilation to prevent further P-SILI, an important contributor to poor outcomes in COVID-19 pneumonia. One of the main limitations of this study was the relatively small study population and we recommend that further studies be conducted to further explore these findings.
Dissertation (M.Med.(Cardiothoracic Surgery))--University of the Free State, 2023
Keywords: Continuous positive airway pressure; COVID-19; High flow nasal cannula; Hyperventilation; Indications for mechanical ventilation; Intensive care unit; Non-invasive positive pressure ventilation; Oxygen therapy; Patient self-induced lung injury; PPE